2002
DOI: 10.1248/jhs.48.555
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Sublethal Assay of Alkylphenol and Organotin Compounds Using the Nematode Caenorhabditis elegans.

Abstract: The free-living nematode, Caenorhabditis elegans (C. elegans) was adopted as a multicellular biosensor of biological toxicity from alkylphenols and organotin compounds. Alkylphenols were found to affect reproduction at lower doses than indicated by the acute toxicity assay. In particular, nonylphenol altered the reproduction rate of C. elegans at a dose 10-to 100-fold lower than the 50% lethal concentration (LC 50 ). A comparison of the number of viable worms and eggs suggested that alkylphenols and organotin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
3
7
0
Order By: Relevance
“…16) In the present study, in all exposed groups also occasionally individuals exhibited an abnormality in the vulva (Fig. 4).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…16) In the present study, in all exposed groups also occasionally individuals exhibited an abnormality in the vulva (Fig. 4).…”
Section: Resultssupporting
confidence: 68%
“…Accordingly, we have established several laboratory-scale bioassay systems to evaluate the impact of various chemicals on C. elegans. [15][16][17][18] Nonylphenol (NP) and bisphenol A (BisA) are known to bind estrogen receptors. Yamakoshi et al reported previously that 4-(1-adamantyl) phenol (AdP) and 4,4′-(1,3-adamantanediyl) diphenol (AdDP) exhibited potent estrogenic activity.…”
mentioning
confidence: 99%
“…A study with the estrogenic compound 4-nonylphenol also showed a concentration-dependent stimulation of reproduction and growth in C. elegans, with first effects at 0.2 and 0.3 lM, respectively (Hö ss et al 2002). Tominaga et al (2002) also found effects of alkylphenols on the reproduction of C. elegans, however, nonylphenol and octylphenol significantly reduced nematode reproduction at concentrations of 0.02-2.0 lM. For the freeliving nematode Cephalobus sp.…”
Section: Effects Of Potential Edcs On Nematodesmentioning
confidence: 85%
“…The presence of estrogen receptors or binding proteins was demonstrated in the free-living nematode species Panagrellus redivivus and Caenorhabditis elegans by Hood et al [38]. An assay with C. elegans was developed for the detection of sublethal effects caused by alkylphenols and organotin compounds [39]. Alkylphenols were found to affect reproduction at low doses.…”
Section: Resultsmentioning
confidence: 99%
“…Alkylphenols were found to affect reproduction at low doses. The technical mixture of 4-isononylphenols decreased the reproduction rate of C. elegans at a concentration of 2.0 mM [39]. Höss et al [40] showed that the structure of nematode communities in freshwater microcosms was altered in the presence of the technical mixture of 4-iso-nonylphenols.…”
Section: Resultsmentioning
confidence: 99%